Application physiotherapy in rehabilitation rheumatoid arthritis - Nogas, Angela; Grygus, Igor; Prymachok, Liudmyla (Journal of Education, Health and Sport, 2017)
Nogas Angela, Grygus Igor, Prymachok Liudmyla. Application physiotherapy in rehabilitation rheumatoid arthritis. Journal of Education, Health and Sport. 2016;6(11):184-194. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166045 http://ojs.ukw.edu.pl/index.php/johs/article/view/3985 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 10.11.2016. APPLICATION PHYSIOTHERAPY IN REHABILITATION RHEUMATOID ARTHRITIS Angela Nogas, Igor Grygus, Liudmyla Prymachok National University of Water and Environmental Engineering Abstract Background: Rheumatoid arthritis is one of the most common forms of inflammatory diseases of the joints. The disease leads to deformation, then to destruction of the diseased joint and to disability. Physiotherapy is used for the treatment and rehabilitation of rheumatoid arthritis. It is assumed that physiotherapy treatments that promote remission of the disease, improve the quality of patients’ life, create the necessary conditions for comprehensive rehabilitation programs. Objective: Systematic’s review conducting of studies that assess the effect of physiotherapy in the rehabilitation of patients with rheumatoid arthritis. Methods: Theoretical analysis of scientific and methodical literature, methods of analysis, synthesis, generalization. Results: To reduce inflammation in the joints is performed UV of affected joints weak or medium erythermal or middle erythermal doses used UHF therapy. UHF-therapy prescribed to the area of joint in I or II dose, duration 10 min., the course – 5-8 treatments. For patients with minimal activity is added electrophoresis NSAIDs. Electrophoresis aspirin is applied on the affected joints (every day, the course – 10-12 procedures), which favorably affect the course of rheumatoid arthritis. Conclusions: Physical therapy can reduce pain and stiffness in the joints, prevent deformity and restore function, improve independence and quality of life. State of the art is a major incentive to develop new activities in the treatment and rehabilitation of patients with rheumatoid arthritis to improve joint functional activity and their physical health. Keywords: rheumatoid arthritis, physiotherapy, rehabilitation, hydrotherapy.